Relationship between the meaning of life and mental health in Honduran university students - Zelaya Guardado, Vilma Odessa (2023)
Several studies have investigated the relationship between the meaning of life and mental health. However, very few deal with higher education students, so this research examines this relationship in Honduran university students. The sample consists of 345 undergraduate students from the San Pedro y San Pablo campus (SPSP) of the Catholic University of Honduras (UNICAH) between 18 and 45 years old, 75.1 % female and 24.9 % male. Most students are at the lower levels of the sense of life (prone to experience noogenic neurosis, show existential emptiness or be in a zone of frustration, alarm, and risk), and 59.4 % manifest psychic alterations. There is also a significant inverse relationship between the meaning of life and mental health and their respective dimensions. The article recommends a preventive and corrective psychological approach to address the problem.